1998
DOI: 10.1111/j.1540-8191.1998.tb01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Exercise Hemodynamics Among Nonstented Aortic Bioprostheses, Mechanical Valves, and Normal Native Aortic Valves

Abstract: Although the mechanical group (SOR) had larger measured EOAI, the greater increase in gradients with exercise in this group suggests that the TORONTO SPV is less obstructive to flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…This allows us to understand the real impact of PPM in hemodynamic terms during physical activity and to correlate valve hemodynamics with clinical symptoms at a certain degree of physical effort. Several studies on bioprostheses have reported a significant increase in mean gradient during exercise, the magnitude of which varies greatly according to the size and type of valve implanted . The impact of this increased pressure drop on both quality of life and survival is not apparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows us to understand the real impact of PPM in hemodynamic terms during physical activity and to correlate valve hemodynamics with clinical symptoms at a certain degree of physical effort. Several studies on bioprostheses have reported a significant increase in mean gradient during exercise, the magnitude of which varies greatly according to the size and type of valve implanted . The impact of this increased pressure drop on both quality of life and survival is not apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that stentless prostheses provide a better hemodynamic performance, especially during exercise, in that the effective orifice area increases as the flow increases . On the other hand, the design of currently available stented valves has improved to such an extent that these valves now provide excellent fluid dynamic performance.…”
mentioning
confidence: 99%
“…Young age (<50 years), especially in patients who are physically active, has been reported as predictor of potential PPM [ 11 , 12 ]. It has therefore been suggested [ 11 , 13 , 14 , 20 ] that in patients requiring a 19 mm valve or smaller, prostheses with the largest actual (nominal) orifice area (AOA) as provided by manufacturer, or other types of valve prostheses, i.e. stentless porcine [ 4 , 13 , 14 , 21 - 25 ], aortic homograft [ 24 ] or pulmonary autograft [ 22 , 23 ] should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a trend towards stentless biological valves (Silberman et al, 1998;Williams et al, 1999;Doss et al, 2005) and valve-sparing procedures (David et al, 2001;Hopkins, 2003). The intention is to create a more physiological valve substitute allowing dynamic root expansion during the systolic phase of the cardiac cycle while maintaining physiological fluid dynamics.…”
Section: Introductionmentioning
confidence: 97%